Determinant Factors of Audit Delay: Evidence on Jakarta Islamic Index (JII) - Ponirah, Ade; Sinta Nurriyah, Laela; Muslih, Amar; Yulianti, Lina; Sakinah, Gina (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
This study aims to analyze the factors that influence audit delay. The method used in this research is to use descriptive analysis with a quantitative approach in the sampling technique using purposive sampling and based on predetermined criteria there are 10 companies with a period of 5 years or as much as 50 data. The statistical test tools used in this study are descriptive statistical analysis, classical assumption test, multiple linear test, coefficient of determination analysis (R2) and hypothesis testing using the t test and f test. The results showed that partially company size, audit opinion and profitability using return on assets had no significant effect on audit delay. Simultaneously, it shows that company size, audit opinion and profitability together have no significant effect on audit delay with the results of the coefficient of determination test (R2 ) the R square value is 0.129 or 12.9%, meaning that the three variables are only able to influence audit delay only by 12.9% and 87.1% by other factors.